Influence of sol counter-ions on the visible light induced photocatalytic behaviour of TiO2 nanoparticles - Tobaldi, D. M.
Titanium dioxide (TiO2) nanoparticles are attracting increasing interest because of their superior photocatalytic and antibacterial properties. Here, aqueous titanium oxy-hydroxide sols were made, using a green synthesis method, from the controlled hydrolysis/peptisation of titanium isopropoxide. Three different mineral acids were used to peptise the sol (HNO3, HBr and HCl), and provide counter-ions. The influence of nitrate or halide sol counter-ions on size distributions of the starting sols were measured via photon correlation spectroscopy (PCS). Semi-quantitative phase composition analysis (QPA), on the gels thermally treated at 450 and 600 degrees C, was carried out via Rietveld refinement of the X-ray powder diffraction (XRD) patterns. Photocatalytic activity of the prepared samples was also assessed, in the gas-solid phase, monitoring NOx degradation using both solar and white lamps (artificial indoor lightning). Both halides (chlorine or bromine) encouraged the anatase-to-rutile phase transition (ART), resulting in powders containing up to 77 wt% rutile and only 5 wt% brookite after heating to only 450 degrees C, with particle sizes similar to 50 nm, and these produced 100% rutile at 600 degrees C. Photocatalytic tests in the gas phase, using a white lamp, showed that the halide-stabilised sols, thermally treated at 450 degrees C, gave titania with the highest NOx conversion rate - twice that of Degussa P25.